Outcome-Based Education in Islamic Religious Education: Academic Outcomes and Students' Spiritual Awareness - Irfan Anshori; Desita Erviani; Putri Yulia Solihah; Mutoharoh Mutoharoh (Universitas Islam Lamongan, 2026)
The implementation of Outcome-Based Education (OBE) has become a dominant paradigm in higher education in Indonesia, particularly in supporting quality assurance and the accountability of learning outcomes. This study aims to analyze the implementation of OBE in Islamic Religious Education (IRE) learning at universities and to examine the extent to which this approach accommodates both students' academic achievement and the development of their spiritual awareness. This research employed a mixed-method approach with a sequential explanatory design. The findings indicate that OBE effectively supports students' academic achievement, which is categorized as high. However, students' spiritual awareness remains at a moderate level and tends to develop implicitly outside the formal evaluation system. These findings highlight the need to integrate spiritual awareness more explicitly within the OBE framework in Islamic Religious Education.